2011
DOI: 10.3390/md9081359
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidan from Marine Brown Algae Inhibits Lipid Accumulation

Abstract: In this study, we elucidated the inhibitory effect of fucoidan from marine brown algae on the lipid accumulation in differentiated 3T3-L1 adipocytes and its mechanism. The treatment of fucoidan in a dose-dependent manner was examined on lipid inhibition in 3T3-L1 cells by using Oil Red O staining. Fucoidan showed high lipid inhibition activity at 200 μg/mL concentration (P < 0.001). Lipolytic activity in adipocytes is highly dependent on hormone sensitive lipase (HSL), which is one of the most important target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 20 publications
0
55
1
3
Order By: Relevance
“…Moreover, recent studies have shown that low molecular weight fucoidan (LMWF) reduces lipid accumulation by retarding the adipogenesis in 3T3-L1 cells (Park et al, 2011). However, although fucoidan is known to regulate many physiologic functions (Cumashi et al, 2007), its effects on insulin resistance and type 2 diabetes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have shown that low molecular weight fucoidan (LMWF) reduces lipid accumulation by retarding the adipogenesis in 3T3-L1 cells (Park et al, 2011). However, although fucoidan is known to regulate many physiologic functions (Cumashi et al, 2007), its effects on insulin resistance and type 2 diabetes are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of fucoidan and its composition strongly depend on the extraction source (the type of algae) and the method of extraction, thereby affecting its effectiveness. Fucoidan extracted from different species has varied biological activities, including anti-coagulant [19], antioxidant [20], immunomodulatory [21], anti-inflammatory [22], antibacterial activity [23], and anti-obesity [24,25] properties. Alternatively, different processing methods are also important factors that influence the molecular conformational changes.…”
Section: Introductionmentioning
confidence: 99%
“…It is also very much recognized that brown seaweeds are a potent inhibitor of lipid accumulation (Park et al, 2011). Thus it could be deduced that increase in brain NE levels of SSET and SMET (oral administration of extracts for four weeks) rats might be due to the lipolytic activity of seaweeds.…”
Section: Discussionmentioning
confidence: 99%